Iron species activating chlorite: Neglected selective oxidation for water treatment - Qihui Xu; Zhipeng Li; Feng Liu; Hong You; Binghan Xie (Environmental Science and Ecotechnology, 2023)
Chlorite (ClO2−) is the by-product of the water treatment process carried out using chlorine dioxide (ClO2) as an effective disinfectant and oxidant; however, the reactivation of ClO2− has commonly been overlooked. Herein, it was unprecedentedly found that ClO2− could be activated by iron species (Feb: Fe0, FeII, or FeIII), which contributed to the synchronous removal of ClO2− and selective oxidative treatment of organic contaminants. However, the above-mentioned activation process presented intensive H+-dependent reactivity. The introduction of Feb significantly shortened the autocatalysis process via the accumulation of Cl− or ClO− during the protonation of ClO2− driven by ultrasonic field. Furthermore, it was found that the interdependent high-valent-Fe-oxo and ClO2, after identification, were the dominant active species for accelerating the oxidation process. Accordingly, the unified mechanisms based on coordination catalysis ([FeN(H2O)a(ClOxm−)b]n+-P) were putative, and this process was thus used to account for the pollutant removal by the Feb-activated protonated ClO2−. This study pioneers the activation of ClO2− for water treatment and provides a novel strategy for “waste treating waste”. Derivatively, this activation process further provides the preparation methods for sulfones and ClO2, including the oriented oxidation of sulfoxides to sulfones and the production of ClO2 for on-site use.